СТРУКТУРА ХАОТИЧЕСКИХ ПРОЦЕССОВ В ПРЕОБРАЗОВАТЕЛЕ НАПРЯЖЕНИЯ - Жуйков, В.Я.; Матийко , А.А. (Інститут електродинаміки НАН України, Київ, 2014)
The structure of the chaotic oscillations in the DC converter is considered in the article. The influence of the transcendental and differential equations solution step on the simulation results is studied. The phenomenon of chaotic oscillations cluster when changing the interval fixing variant between key switching points is considered. References 5, table 1, figure 1.